Clean preparation method of industrial solid waste-based CaM-LDHs and its application in gas deacidification

Through the clean preparation method of industrial solid waste base CaM-LDHs, the two-step ball milling method and self-heating technology are used to solve the problems of low utilization rate of industrial solid waste resource and complex preparation process, and high-efficiency and low-cost calcium Basic hydrotalc preparation and acid gas removal performance.

CN118949677BActive Publication Date: 2024-12-27SHANDONG AVIC TIANYE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411442640.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2024-12-27
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The utilization rate of industrial solid waste is low, and the preparation process of LDHs is complex and expensive, so it is not suitable for industrial applications.

Method used

The cleaning preparation method of industrial solid waste-based CaM-LDHs, including calcium carbide slag, steel slag, activated calcium oxide and desulfurization ash as raw materials, and calcium-based hydrotalcite is prepared by dry and wet ball milling method, and energy consumption is reduced by self-heating. And use synergists to improve preparation efficiency.

Benefits of technology

The high added value of calcium-based hydrotalcite preparation is achieved, which reduces production costs, simplifies the process flow, reduces waste liquid generation, improves resource utilization efficiency, and shows efficient acid gas removal performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118949677B_ABST
    Figure CN118949677B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of energy-saving and environmental protection technology, and specifically to a clean preparation method of industrial solid waste-based CaM-LDHs and its application in gas deacidification. Industrial solid waste steel slag and carbide slag are used as metal cation sources, desulfurization ash is used as anion source, and active calcium oxide is used as a heat source. A synergist-promoted "self-heating" assisted dry-wet two-step ball milling method is used to prepare CaM-LDHs. The CaM-LDHs prepared by the present invention exhibits high deacidification efficiency and good stability for SO2, HCl, and HF in industrial gases; compared with the traditional LDHs preparation method, the method of the present invention greatly reduces the amount of water and the generation of waste liquid, reduces environmental pollution, and can not only achieve clean, rapid and large-scale production of LDHs, but also realize the resource and high-value utilization of industrial solid waste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy conservation and environmental protection, and in particular to a clean preparation method of industrial solid waste-based CaM-LDHs and an application thereof in gas deacidification. Background Art

[0002] As environmental protection standards become increasingly stringent, not only must the concentration of pollutants in flue gas be strictly controlled, but the generation and disposal of solid waste are also receiving more and more attention. In the context of "dual carbon", it is urgent to strengthen the comprehensive utilization of solid waste.

[0003] Steel slag is a large solid waste generated during the steel smelting process. The storage of large amounts of steel slag not only occupies farmland and land, but also pollutes groundwater. The main chemical components of steel slag are CaO, SiO2, Al2O3, Fe2O3, MgO and a small amount of f-CaO, MnO, FeO, P2O5 and metal Fe. Steel slag can be used to remove acidic gases due to its rich alkaline oxides. However, most of the effective components in steel slag exist in mineral phases and have a dense structure, which makes it difficult to directly participate in the deacidification reaction and must be treated before use. Calcium carbide slag is the waste slag produced in the process of producing acetylene by calcium carbide hydrolysis, and its main component is Ca(OH)2. With the rapid increase in PVC production, my country's annual discharge of calcium carbide slag has maintained tens of millions of tons. The output of calcium carbide slag is large, the water content is high, and the pH value of the slag liquid is generally greater than 12, which poses certain hazards to the environment. It is necessary to recycle calcium carbide slag to reduce the environmental pressure of enterprises and the harm to the natural environment. Baking soda flue gas desulfurization technology is widely used in flue gas desulfurization projects in non-electric industries due to its advantages such as low initial investment and small equipment footprint. However, there is currently a lack of effective comprehensive utilization methods for the desulfurization ash produced by the baking soda desulfurization process. The stacking of baking soda desulfurization ash requires a large amount of land and causes many environmental problems. Although there are many reports on the resource utilization of industrial solid waste, most technologies are still at the stage of inefficient and extensive utilization, resulting in limited product added value and unclear economic benefits. Therefore, it is urgent to strengthen the research and development of new technologies and new paths for the high value and resource utilization of industrial solid waste in order to improve resource utilization efficiency, increase economic benefits, and respond to the country's environmental protection and sustainable development strategies.

[0004] Layered Double Hydroxides (LDHs) are a type of layered ionic compounds with a brucite Mg(OH)2 type regular octahedral structure, which is assembled by the interaction of positively charged main layers and interlayer anions through non-covalent bonds. The general chemical formula of LDHs is generally expressed as: , where x is M 3+ The molar fraction of M in metal ions ranges from 0.2 to 0.33. 2+Represents divalent metal cations, including Mg 2+ , Ca 2+ , Ni 2+ ,Co 2+ , Zn 2+ , Cu 2+ etc., M. 3+ Represents trivalent metal cations, including Al 3+ , Fe 3+ ,Cr 3+ etc. n- Anions used to balance non-framework charges, including CO3 2- , NO3 - , SO4 2- , Cl - etc. inorganic and organic ions and complex ions. Due to its unique layered structure, hydrotalcite has controllable characteristics in terms of the chemical composition of the main layer, the type and quantity of the interlayer guest anions, and the particle size and distribution of the intercalated assembly. Therefore, hydrotalcite is widely used in the fields of adsorption, catalysis, medicine, flame retardancy, photochemistry, ion exchange, etc.

[0005] With the continuous expansion of the application field of hydrotalcite, the research on the preparation process of hydrotalcite has also been rapidly developed. At present, the more mature methods for preparing hydrotalcite mainly include coprecipitation method, ion exchange method, urea method, hydrothermal method, roasting recovery method and nucleation / crystallization separation method. However, these methods will produce more waste liquid and by-products, and their production cost is too high and the utilization rate of raw materials is low, which limits their industrial production and application. Therefore, some researchers began to explore the clean preparation method of LDHs. For example, CN107902681A discloses a preparation method of calcium aluminum hydrotalcite, in which calcium hydroxide, aluminum hydroxide and sodium carbonate are added to a ball mill, and after dry grinding for 2 to 4 hours, the solid mixture is mixed with water, and microwave hydrothermal crystallization is carried out at 70 to 90 ° C for 5 to 20 minutes. After washing, filtering and drying, calcium aluminum hydrotalcite is obtained. Chinese patent CN105271343A discloses a method for producing hydrocalumite, wherein calcium hydroxide and aluminum hydroxide are added to a ball mill, and hydrocalumite is obtained through processes such as dry grinding, wet grinding, water bath crystallization, and centrifugal drying. Chinese patent CN117163991A discloses a method for preparing magnesium aluminum hydrotalcite based on mechanical grinding, specifically, firstly mixing magnesium compound, aluminum compound and sodium carbonate powder with a certain amount of water and organic solvent, and then heating and ball milling, and then washing, filtering and drying to obtain a magnesium aluminum hydrotalcite product. The above patent reduces the water consumption and total reaction time by using mechanical grinding, but still uses various forms of heating crystallization operations, which has high energy consumption, and still needs to use a large amount of water to clean the impurity phase in the sample after crystallization, and the amount of waste liquid is high. The step-by-step operation increases the complexity, thereby limiting the large-scale production and industrial application of LDHs. Summary of the invention

[0006] The present invention provides a clean preparation method of industrial solid waste-based CaM-LDHs and its application in gas deacidification, so as to solve the problems of low resource utilization rate of industrial solid waste and complex LDHs preparation process, high cost and unsuitability for industrial application.

[0007] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0008] The clean preparation method of industrial solid waste-based CaM-LDHs is specifically prepared from the following raw materials, including four raw materials: carbide slag, steel slag, activated calcium oxide, and desulfurization ash, and a synergist. Among them, the mass ratio of carbide slag: steel slag: activated calcium oxide: desulfurization ash is (0.5-8): (1-7): (0.1-1): (1.4-5).

[0009] Preferably: the synergist is divided into two parts: synergist a and synergist b, wherein the synergist a is one of sodium polyacrylate, sodium stearate and sodium polycarboxylate, and its dosage is 0.5-5% of the total amount of the four raw materials; the synergist b is a mixed solvent of alcohol, alcohol amine and water, and its dosage is 0.25-1 times of the total amount of the four raw materials;

[0010] Wherein, the volume ratio of the total volume of alcohol and alcohol amine to water is (0.05-0.75):1, and the volume ratio of the alcohol to alcohol amine is (1-6):(1-4);

[0011] Wherein, the alcohol is one or two of ethanol, ethylene glycol, and propylene glycol; the alcohol amine is one of N-methyldiethanolamine and isobutanolamine.

[0012] Preferably, the mass content of Ca(OH)2 in the carbide slag is 82-92%, the moisture content is 1-5%, and the particle size is 45-75 μm.

[0013] Preferably: the steel slag comes from waste generated by steel enterprises in steelmaking production, and is one or more of refined slag, converter slag and electric furnace slag, and is ground into fine powder; wherein the mass content of CaO is 35-50%, the mass content of MgO is 5-12%, the mass content of FeO and Fe2O3 is 15-30%, the mass content of Al2O3 is 2.5-10%, and the particle size is 45-75μm.

[0014] Preferably, the desulfurization ash is a by-product of baking soda dry desulfurization, and its main components are: 60-72% Na2SO4, 15-24% Na2CO3 and 6-10% NaCl, and the particle size is 45-75 μm.

[0015] Preferably, the active calcium oxide has an effective calcium oxide content of >80%, an activity of >300, a raw or over-burned content of <6%, and a particle size of 45-75 μm.

[0016] Specifically, the clean preparation method of industrial solid waste-based CaM-LDHs comprises the following preparation steps:

[0017] Step 1: weigh a certain mass of carbide slag, steel slag, active calcium oxide and desulfurization ash in sequence according to a mass ratio of (0.5-8): (1-7): (0.1-1): (1.4-5), mix the four raw material powders evenly, add synergist a thereto, and then place them in a high-speed planetary ball mill for dry grinding, the ball-to-material mass ratio is controlled at (7-11): 1, the ball mill speed is 300-1000 r / min, and the dry grinding is performed for 0.5-3 hours to obtain a solid mixture A;

[0018] Step 2: Weigh a certain amount of synergist and add it to mixture A in a mass ratio of (0.25-1):1, continue wet grinding for 0.5-3h, and then put the obtained product into a constant temperature forced air drying oven and dry it at 60-130°C for 2-8 hours to obtain the product CaM-LDHs;

[0019] Step 3: The dried product is transferred to a tube furnace and calcined at 300-700° C. for 2-5 h in an air atmosphere to finally obtain CaM-LDHs derivative oxide CaM-LDOs.

[0020] The CaM-LDHs and its derivative oxides can be used to remove acid gases such as SO2, HF, and HCl in a wide temperature window; the acid gases come from blast furnace gas produced as a byproduct of the blast furnace ironmaking process, and industrial kilns such as tunnel kilns, rotary kiln heating furnaces, and hot blast furnaces. The mass concentration ranges of SO2, HF, and HCl are 50 to 2000 mg / m 3 , 10~200mg / m 3 and 10–200 mg / m 3 The reaction temperature is 75-300°C, the reaction pressure is normal pressure-0.3Mpa, and the space velocity is 500-10000h -1 .

[0021] Technical effects and advantages of the present invention:

[0022] 1. The present invention converts industrial solid waste steel slag, carbide slag and desulfurization ash into calcium-based hydrotalcite with high added value, which not only reduces the environmental impact of the waste, realizes the resource utilization of waste, but also brings economic benefits; on the other hand, these solid waste-based raw materials are widely available and low in price, which effectively reduces the production and use costs of calcium-based hydrotalcite, and is conducive to large-scale production.

[0023] 2. The present invention adopts a "self-heating" assisted dry-wet two-step ball milling method to prepare calcium-based hydrotalcite-like products. The high-energy collision between the grinding balls and the raw materials is utilized to strengthen the mass transfer and reaction process, thereby realizing the rapid preparation of the target hydrotalcite-like products. By controlling the grinding parameters, such as time, rotation speed and grinding media, a hydrotalcite-like product with uniform and stable properties can be obtained.

[0024] 3. Compared with the traditional liquid phase synthesis method, the preparation method provided by the present invention is simpler, the conditions are easy to control, the yield of hydrotalcite-like substances is higher, and the entire preparation process greatly reduces the amount of water used and the generation of waste liquid, reduces environmental pollution, is highly environmentally friendly, and can achieve clean production.

[0025] 4. Compared with the traditional mechanical synthesis method, the method provided by the present invention does not require an external heat source and adopts a "self-heating" method, that is, using the heat released by the active calcium oxide digestion reaction to accelerate the rapid nucleation and growth of CaM-LDHs crystals. This method consumes less energy and is more low-carbon and environmentally friendly, and can achieve clean production.

[0026] 5. The calcium-based hydrotalcite material prepared by the present invention has well-developed pores, large specific surface area, and a large number of alkaline active centers, and can be used for the efficient removal of acidic gases such as SO2, HCl, and HF.

[0027] 6. The present invention innovatively uses a synergist, which has the following benefits: first, it aids grinding and dispersion, improves the grindability of solid waste raw materials, and avoids powder agglomeration and wall adhesion during ball milling; second, it can also play a structural guiding role in the crystallization process of CaM-LDHs, which will prompt CaM-LDHs to form a looser and more porous structure; finally, after high-temperature calcination of CaM-LDHs, the amine substances contained therein are converted into structural alkaline centers containing N on the surface of the material, which plays a role in increasing the alkalinity of the material surface, thereby making it exhibit more efficient and stable deacidification performance.

[0028] The present invention uses industrial solid waste steel slag and carbide slag as metal cation sources and desulfurization ash as anion source, and adopts a dry-wet two-step ball milling method to prepare calcium-containing hydrotalcites (CaM-LDHs). During the entire preparation process, no additional heating is required, but a "self-heating" method is adopted, that is, by adding active calcium oxide to the raw materials, the heat released during its digestion process is used to accelerate the nucleation and growth of hydrotalcites; in addition, the entire preparation process of the calcium-based hydrotalcites in the present invention does not require complex operations such as water washing and solid-liquid separation, and has the advantages of low cost, green energy saving, simple operation, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. The embodiments of the present invention are provided for the purpose of illustration and description, and are not intended to be exhaustive or to limit the present invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention, and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.

[0031] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the art can be used. If no manufacturer is specified for the reagents or instruments used, they are all commercially available conventional reagent products.

[0032] Evaluation method for material deacidification performance: A fixed bed reactor is used to test the material's removal performance for acidic gases SO2, HCl, and HF. The temperature of the reactor is precisely controlled by a vertical tube furnace. The mass concentration ranges of SO2, HF, and HCl in the simulated gas are 50 to 2000 mg / m 3 , 10~200mg / m 3 and 10–200 mg / m 3 , 11% O2, N2 as balance gas, reaction temperature is 100-300℃, reaction pressure is normal pressure-0.3Mpa, space velocity is 500-10000h -1 .

[0033] The contents of SO2, HCl and HF in the flue gas before and after the reaction were detected by Fourier infrared gas analyzer, and the changes of deacidification efficiency over time were observed. The calculation formula of the specific evaluation index deacidification efficiency R (%) is as follows:

[0034] ;

[0035] Where: C in : Inlet concentration of SO2, HCl or HF (mg / m 3 ), C out : outlet concentration of SO2, HCl or HF (mg / m 3 ). Example 1

[0036] In this embodiment, a clean preparation method of industrial solid waste-based CaM-LDHs is provided, comprising the following steps:

[0037] Step 1: Weigh 30.8g of carbide slag, 38.5g of steel slag, 3.8g of active calcium oxide, and 26.9g of desulfurization ash, mix the above four raw material powders evenly, add 2.5g of sodium polyacrylate thereto, and then place the mixture in a high-speed planetary ball mill for dry grinding, the ball-to-material mass ratio is 10:1, the ball mill speed is 500r / min, and the dry grinding is carried out for 2h to obtain a solid mixture A;

[0038] Step 2: Take a uniform mixture of 5 ml of ethanol, 5 ml of propylene glycol, 5 ml of N-methyldiethanolamine and 35 ml of water, add it to the mixture A, continue wet grinding for 2 hours, and then put the resulting product into a constant temperature forced air drying oven and dry it at 80°C for 5 hours to obtain the product CaM-LDHs.

[0039] Step 3: The dried product was transferred to a tube furnace and calcined at 400 °C for 4 h in an air atmosphere to finally obtain the CaM-LDHs derivative oxide CaM-LDOs.

[0040] Activity test conditions: A fixed bed reactor was used to test the removal performance of the material for acidic gases SO2, HCl, and HF. The temperature of the reactor was precisely controlled by a vertical tube furnace. The mass concentration ranges of SO2, HF, and HCl in the simulated gas were 50 mg / m 3 , 10mg / m 3 and 100 mg / m 3 , 11% O2, N2 as balance gas, reaction temperature is 200℃, normal pressure, space velocity is 8000h -1 .

[0041] Analysis of experimental results: The concentration changes of SO2, HCl and HF in the gas before and after the reaction were detected using a Fourier infrared gas analyzer, and it was found that the removal rates of SO2, HCl and HF could reach 98.4%, 95.1% and 92.8%, respectively. Example 2

[0042] In this embodiment, a clean preparation method of industrial solid waste-based CaM-LDHs is provided, comprising the following steps:

[0043] Step 1: Weigh 38.3g of carbide slag, 33.5g of steel slag, 4.8g of active calcium oxide, and 23.4g of desulfurization ash, mix the above four powders evenly, add 0.5g of sodium polycarboxylate thereto, and then place the mixture in a high-speed planetary ball mill for dry grinding, the ball-to-material mass ratio is 9:1, the ball mill speed is 800r / min, and the dry grinding is 1.5h to obtain a solid mixture A;

[0044] Step 2: Measure 2.5 ml of propylene glycol, 2.5 ml of isobutanolamine and 95 ml of water to form a synergist B, add it to the mixture A, continue wet grinding for 1.5 hours, and then put the resulting product into a constant temperature forced air drying oven and dry it at 60°C for 7 hours to obtain the product CaM-LDHs.

[0045] Step 3: The dried product was transferred to a tube furnace and calcined at 500°C for 3 h in an air atmosphere to finally obtain the CaM-LDHs derivative oxide CaM-LDOs.

[0046] Activity test conditions: A fixed bed reactor was used to test the removal performance of the material for acidic gases SO2, HCl, and HF. The temperature of the reactor was precisely controlled by a vertical tube furnace. The mass concentration ranges of SO2, HCl, and HF in the simulated gas were 500 mg / m 3 , 200mg / m 3 and 50 mg / m 3 , 11% O2, N2 as balance gas, reaction temperature is 250℃, normal pressure, space velocity is 5000h -1 .

[0047] Analysis of experimental results: The concentration changes of SO2, HCl and HF in the gas before and after the reaction were detected using a Fourier infrared gas analyzer, and it was found that the removal rates of SO2, HCl and HF were 95.8%, 89.3% and 93.2%, respectively. Example 3

[0048] In this embodiment, a clean preparation method of industrial solid waste-based CaM-LDHs is provided, comprising the following steps:

[0049] Step 1: Weigh 22.2g of carbide slag, 44.4g of steel slag, 2.2g of active calcium oxide, and 31.1g of desulfurized ash, mix the above four powders evenly, add 2.5g of sodium stearate thereto, and then place the mixture in a high-speed planetary ball mill for dry grinding, the ball-to-material mass ratio is 7:1, the ball mill speed is 1000r / min, and the dry grinding is performed for 0.5h to obtain a solid mixture A;

[0050] Step 2: Measure 2.5 ml of propylene glycol, 7.5 ml of N-methyldiethanolamine and 15 ml of water to form a synergist B, add it to the mixture A, continue wet grinding for 0.5 h, and then put the resulting product into a constant temperature forced air drying oven and dry it at 130°C for 2 hours to obtain the product CaM-LDHs.

[0051] Step 3: The dried product is transferred to a tube furnace and calcined at 600°C for 2 h in an air atmosphere to finally obtain the CaM-LDHs derivative oxide CaM-LDOs.

[0052] Activity test conditions: A fixed bed reactor was used to test the removal performance of the material for acidic gases SO2, HCl, and HF. The temperature of the reactor was precisely controlled by a vertical tube furnace. The mass concentration ranges of SO2, HCl, and HF in the simulated gas were 1000 mg / m 3 , 50mg / m 3 and 150 mg / m 3 , 11% O2, N2 as balance gas, reaction temperature 175℃, normal pressure, space velocity 1000h -1 .

[0053] Analysis of experimental results: The concentration changes of SO2, HCl and HF in the gas before and after the reaction were detected using a Fourier infrared gas analyzer, and it was found that the removal rates of SO2, HCl and HF were 94.2%, 88.7% and 89.3%, respectively. Example 4

[0054] In this embodiment, a clean preparation method of industrial solid waste-based CaM-LDHs is provided, comprising the following steps:

[0055] Step 1: Weigh 16.0g of carbide slag, 48.0g of steel slag, 2.4g of active calcium oxide, and 33.6g of desulfurization ash, mix the above four powders evenly, add 5g of sodium polyacrylate thereto, and then place the mixture in a high-speed planetary ball mill for dry grinding, the ball-to-material mass ratio is 8:1, the ball mill speed is 300r / min, and the dry grinding is performed for 3h to obtain a solid mixture A;

[0056] Step 2: Measure the synergist B prepared by mixing 5 ml of ethanol, 10 ml of ethylene glycol, 10 ml of isobutanolamine and 50 ml of water, add it to the mixture A, continue wet grinding for 3 h, and then put the resulting product into a constant temperature forced air drying oven and dry it at 100°C for 4 hours to obtain the product CaM-LDHs.

[0057] Step 3: The dried product was transferred to a tube furnace and calcined at 300°C for 5 h in an air atmosphere to finally obtain the CaM-LDHs derivative oxide CaM-LDOs.

[0058] Activity test conditions: A fixed bed reactor was used to test the removal performance of the material for acidic gases SO2, HCl, and HF. The temperature of the reactor was precisely controlled by a vertical tube furnace. The mass concentration ranges of SO2, HCl, and HF in the simulated gas were 2000 mg / m 3 , 100mg / m 3 and 10 mg / m 3 , 11% O2, N2 as balance gas, reaction temperature at 300℃, atmospheric pressure, space velocity at 500h -1 .

[0059] Analysis of experimental results: The concentration changes of SO2, HCl and HF in the gas before and after the reaction were detected using a Fourier infrared gas analyzer, and it was found that the removal rates of SO2, HCl and HF were 97.6%, 90.5% and 96.5%, respectively. Comparative Example 1

[0060] As a comparative example of Example 1, the difference is that instead of using two-step ball milling, CaM-LDHs is prepared by a one-step ball milling method, and the specific process is as follows:

[0061] Step 1: Weigh 30.8g of carbide slag, 38.5g of steel slag, 3.8g of active calcium oxide and 26.9g of desulfurized ash, mix the above four raw material powders evenly, and add 2.5g of sodium polyacrylate, 5ml of ethanol, 5ml of propylene glycol, 5ml of N-methyldiethanolamine and 35ml of water to the mixture. Then, place the mixture in a high-speed planetary ball mill for 4h, with a ball-to-material mass ratio of 10:1 and a ball milling speed of 500r / min to obtain the product;

[0062] Step 2: Place the obtained product in a constant temperature forced air drying oven and dry it at 80°C for 5 hours to obtain the product CaM-LDHs.

[0063] Step 3: The dried product was transferred to a tube furnace and calcined at 400 °C for 4 h in an air atmosphere to finally obtain the CaM-LDHs derivative oxide CaM-LDOs.

[0064] The activity test conditions were the same as those in Example 1.

[0065] Analysis of experimental results: The concentration changes of SO2, HCl and HF in the gas before and after the reaction were detected by Fourier infrared gas analyzer, and it was found that the removal rates of SO2, HCl and HF were 89.8%, 82.2% and 83.4% respectively. Compared with Example 1, it was found that the deacidification effect of the sample prepared by the one-step ball milling method was significantly lower than that of the sample prepared by the dry and wet two-step ball milling method. It shows that through reasonable proportion design and optimization of ball milling conditions, the two-step ball milling method can achieve uniform dispersion of raw materials and promote the formation of active sites, which is crucial for the activity and stability of the deacidification agent. Comparative Example 2

[0066] As a comparison with Example 2, the difference is that no synergist is used, only 100 ml of water is added during the wet grinding stage, and the remaining preparation steps are the same. The activity test conditions are the same as in Example 2.

[0067] Analysis of experimental results: The concentration changes of SO2, HCl, and HF in the gas before and after the reaction were detected by Fourier infrared gas analyzer, and it was found that the removal rates of SO2, HCl, and HF were 87.5%, 79.6%, and 85.8%, respectively. Compared with Example 2, it was found that when only water was used as a synergist, the deacidification efficiency decreased a lot. The reason is that the organic matter and organic solvent in the synergist played multiple roles in the process of preparing CaM-LDHs by dry and wet two-step ball milling, such as dispersion medium, auxiliary chemical reaction, control of morphology structure, and providing stability. These effects jointly ensure the efficient preparation and excellent deacidification performance of CaM-LDHs, reflecting the irreplaceable nature of the synergist. Comparative Example 3

[0068] As a comparative example of Example 3, the difference is that no active calcium oxide is used, and the remaining steps are the same.

[0069] The activity test conditions are the same as those in Example 3.

[0070] Analysis of experimental results: The concentration changes of SO2, HCl, and HF in the gas before and after the reaction were detected by Fourier infrared gas analyzer, and it was found that the removal rates of SO2, HCl, and HF were 85.1%, 81.7%, and 78.2%, respectively. Compared with Example 3, it was found that when active calcium oxide was not used, its deacidification efficiency decreased significantly. The reason is that active calcium oxide plays multiple roles in providing alkaline sources, enhancing reaction activity, and improving pore structure in the process of preparing deacidification agent by dry and wet two-step ball milling. These effects jointly ensure the high efficiency and economy of CaM-LDHs in practical applications, and provide reliable technical support for controlling acid gas emissions.

[0071] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.

Claims

1. A clean preparation method of industrial solid waste-based CaM-LDHs, characterized in that: The preparation steps include: Step 1: weigh a certain mass of carbide slag, steel slag, active calcium oxide and desulfurization ash in sequence according to a mass ratio of (0.5-8): (1-7): (0.1-1): (1.4-5), mix the four raw material powders evenly, add synergist a thereto, and then place them in a high-speed planetary ball mill for dry grinding, the ball-to-material mass ratio is controlled at (7-11): 1, the ball mill speed is 300-1000 r / min, and the dry grinding is performed for 0.5-3 hours to obtain a solid mixture A; Step 2: Weigh a certain amount of synergist b and add it to mixture A at a mass ratio of (0.25-1):1, continue wet grinding for 0.5-3 hours, and then put the obtained product into a constant temperature forced air drying oven and dry it at 60-130°C for 2-8 hours to obtain the product CaM-LDHs; Step 3: The dried product is transferred to a tube furnace and calcined at 300-700°C for 2-5h in an air atmosphere to finally obtain CaM-LDHs derivative oxide CaM-LDOs; The synergist a is one of sodium polyacrylate, sodium stearate, sodium polycarboxylate; The synergist b is a mixed solvent of alcohol, alcoholamine and water.

2. The clean preparation method of industrial solid waste-based CaM-LDHs according to claim 1, characterized in that: The dosage of the synergist a is 0.5-5% of the total amount of the four raw materials; the dosage of the synergist b is 0.25-1 times of the total amount of the four raw materials; The volume ratio of the total volume of alcohol and alcohol amine to water is (0.05-0.75):1, and the volume ratio of the alcohol to alcohol amine is (1-6):(1-4); Wherein, the alcohol is one or two of ethanol, ethylene glycol, and propylene glycol; the alcohol amine is one of N-methyldiethanolamine and isobutanolamine.

3. The clean preparation method of industrial solid waste-based CaM-LDHs according to claim 1, characterized in that: The mass content of Ca(OH)2 in the carbide slag is 82-92%, the moisture content is 1-5%, and the particle size is 45-75 μm.

4. The clean preparation method of industrial solid waste-based CaM-LDHs according to claim 1, characterized in that: The steel slag comes from waste generated by steel enterprises in steelmaking production, and is one or more of refined slag, converter slag and electric furnace slag, and is obtained by grinding into fine powder; wherein the mass content of CaO is 35-50%, the mass content of MgO is 5-12%, the mass content of FeO and Fe2O3 is 15-30%, the mass content of Al2O3 is 2.5-10%, and the particle size is 45-75μm.

5. The clean preparation method of industrial solid waste-based CaM-LDHs according to claim 1, characterized in that: The desulfurization ash is a by-product of baking soda dry desulfurization, and its composition is: 60-72% Na2SO4, 15-24% Na2CO3 and 6-10% NaCl, and the particle size is 45-75 μm.

6. The clean preparation method of industrial solid waste-based CaM-LDHs according to claim 1, characterized in that: The active calcium oxide has an effective calcium oxide content of >80%, an activity of >300, a raw over-burned content of <6%, and a particle size of 45 to 75 μm.

7. Application of industrial solid waste-based CaM-LDHs obtained by the preparation method according to any one of claims 1 to 6 in gas deacidification, characterized in that: The prepared CaM-LDHs and derived oxides are used as deacidification agents for removing acid gases from industrial gases under a wide temperature window.

8. The use according to claim 7, characterized in that: The acidic gases in the industrial gas include SO2, HF, and HCl.

9. The use according to claim 8, characterized in that: The acidic gases in the industrial gas come from the blast furnace gas produced as a byproduct of the blast furnace ironmaking process and the flue gas generated by industrial kilns, including tunnel kilns, rotary kiln heating furnaces and hot blast furnaces during production; the mass concentration ranges of SO2, HF and HCl are 50-2000 mg / m 3 , 10~200mg / m 3 and 10–200 mg / m 3 The reaction temperature is 75-300°C, the reaction pressure is normal pressure-0.3Mpa, and the space velocity is 500-10000h -1 .